Psychologies of Ageing Theory, Research and Practice (Springer International Publishing, 2018)
This book brings together a diversity of perspectives on the psychology of ageing. Exploring theoretical, conceptual, empirical and practical viewpoints on the topic, the authors offer insight into a range of contemporary issues. Dedicated chapters discuss themes within social and critical psychology such as ageing identities, sexuality and empathy in palliative care. The second part of the book analyses cognitive and biological aspects of ageing, including stress and health in ageing, dementia and lifestyle, and resilience in frailty in old age. The authors conclude by offering perspectives on community and political psychology, examining home and community supports for older people. Written in an accessible style suitable for students as well as researchers in psychology and the social sciences interested in ageing, this book showcases key theoretical, empirical, and practical issues in later life.